2019
DOI: 10.31557/apjcp.2019.20.3.863
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Neutrophil-to-Lymphocyte ratio (NLR) and Platelet-to-Lymphocyte Ratio (PLR) as a Predictive Value of Hematological Markers in Cervical Cancer

Abstract: Background:Inflammation represents a pivotal role in the progression of cervical cancer. The hematological markers of inflammation in complete blood count (CBC) panel are potentially useful in determining the prognosis of the disease.Objective:The aim of the study was to investigate whether the pretreatment neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) could be used as in predicting the stage of cervical cancer.Methods:A retrospective cross-sectional study involving 282 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 28 publications
3
72
0
12
Order By: Relevance
“…NLR is closely associated with most common inflammatory biomarkers, such as C-reactive protein and erythrocyte sedimentation rate (44)(45)(46)(47)(48)(49). A growing body of evidence suggests that NLR may act as excellent indicator of inflammation status in various diseases, such as Crohn's disease (49), cancer (50,51), infection (52,53), and rheumatic diseases (54)(55)(56). Moreover, numerous studies also reported that NLR was closely related to inflammatory response and SLE disease activity (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: ' Discussionmentioning
confidence: 99%
“…NLR is closely associated with most common inflammatory biomarkers, such as C-reactive protein and erythrocyte sedimentation rate (44)(45)(46)(47)(48)(49). A growing body of evidence suggests that NLR may act as excellent indicator of inflammation status in various diseases, such as Crohn's disease (49), cancer (50,51), infection (52,53), and rheumatic diseases (54)(55)(56). Moreover, numerous studies also reported that NLR was closely related to inflammatory response and SLE disease activity (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: ' Discussionmentioning
confidence: 99%
“…Regardless of the exclusion criteria made based on patient medical history and brief finding of an acute inflammatory state other than AMI on the medical report, other more specific supporting examination is needed to rule out those circumstances in the future study. 3 (13,6) This significant result is a requirement to perform post hoc test. Using the least significance different (LSD), it was found that there was a significant difference of NLR mean between low and high GRACE score group.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian sebelumnya menunjukkan bahwa parameter laboratorium seperti penggunaan rasio neutrofil dan limfosit (NLR) dapat dipergunakan sebagai nilai prediktif dalam menentukan keganasan kanker serviks dengan sensitivitas tinggi. 6 Akan tetapi upaya skrining menggunakan pemeriksaan histopatologi seperti pap smear lebih sering dipergunakan masyarakat berkembang. Dengan dilakukan skrining pun, masyarakat dapat menjadi tahu bagaimana keadaannya sehingga jika hasilnya positif, masyarakat dapat melakukan terapi yang lebih dini agar prognosis dari kanker serviks tersebut menjadi lebih baik.…”
Section: Abstrakunclassified